(untitled) (Research, Society and Development, 2022)
The aim of this study was to describe the trend and profile of epidemiological congenital anomalies (CA) in newborns in the State of São Paulo, from 2000 to 2019 and to analyze possible factors associated with the disease. Ecological time series study, using data from Live Births Information System (SINASC). Congenital anomalies and Live births number were extracted from SINASC to calculate incidence. Linear regression models were estimated for number of births with anomalies and for incidence of anomalies, on the basis of year. To analyze the associations of CA with the characteristics of the mother, prenatal/delivery and newborn, the chi-square test was used. Test significance level of 5%. In the analyzed period 12.364.643 births occurred in the state of São Paulo, of which 119.746 showed congenital anomalies (incidence of 0.97%, or 9.7 cases per 1,000 live births). A significant increase in the incidence of congenital anomalies (per 1,000 live births) was observed in the State of São Paulo in 2000 (5.72) and 2019 (12.54). There was an association of CA with maternal variables (age ≥40 years, schooling ≥12 years, mothers without a partner). Related to prenatal care/delivery (none and 1-3 prenatal consultations, duration of preterm pregnancy < 37 weeks, triple deliveries or more and operative); newborns (male, black, brown and yellow race/color, low birth weight <2,500g, and Apgar score from 0 to 3 in the 1st-5th). It is necessary to know the tendency and distribution of congenital anomalies for better targeting of Public Policies related to the binomial.